Oxide Dispersion Strengthened Steels: Precipitation Kinetics and Matrix Phase Transformation - Unegbu, Hyginus Chidiebere Onyekachi; Yawas, Danjuma S.; Asabe, B Dan; Alabi, A A (JMES The International Journal of Mechanical Engineering and Sciences, 2025)
This study presents a comprehensive investigation of the microstructural features, precipitation kinetics, phase transformations, and mechanical properties of Oxide Dispersion Strengthened (ODS) steels, with a focus on the impact of Y₂O₃ particle dispersion. Detailed microstructural analysis using Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM) revealed a fine and uniform distribution of Y₂O₃ particles, averaging 10-15 nm in size, which contributed to significant grain refinement to 5-7 µm. The precipitation kinetics, examined through Differential Scanning Calorimetry (DSC) and dilatometry, showed a diffusion-controlled mechanism with an activation energy of 230 kJ/mol. The dispersed oxide particles delayed the austenite-to-martensite transformation, stabilizing the austenitic phase at higher temperatures, as confirmed by in-situ High-Temperature X-ray Diffraction (HT-XRD). Mechanical tests demonstrated a hardness of 320 HV and a tensile strength of 600 MPa, with a total elongation of 12%. These results highlight the effectiveness of oxide dispersion in enhancing the mechanical strength and thermal stability of ODS steels. The findings suggest that ODS steels are highly suitable for high-performance applications, particularly in environments such as nuclear reactors and aerospace, where high temperature, radiation resistance, and mechanical durability are critical. Future work should explore the long-term stability of these materials under operational conditions to further optimize their performance.